Integrated optical gyroscope using active Long-range surface plasmon-polariton waveguide resonator - Zhang, Tong (Nature Publishing Group, 2014)
Optical gyroscopes with high sensitivity are important rotation sensors for inertial navigation systems. Here, we present the concept of integrated resonant optical gyroscope constructed by active long-range surface plasmon-polariton (LRSPP) waveguide resonator. In this gyroscope, LRSPP waveguide doped gain medium is pumped to compensate the propagation loss, which has lower pump noise than that of conventional optical waveguide. Peculiar properties of single-polarization of LRSPP waveguide have been found to significantly reduce the polarization error. The metal layer of LRSPP waveguide is electro-optical multiplexed for suppression of reciprocal noises. It shows a limited sensitivity of ~10(−4) deg/h, and a maximum zero drift which is 4 orders of magnitude lower than that constructed by conventional single-mode waveguide.